Mothers' non-standard working and childcare-related challenges: A comparison between lone and coupled mothers. Issue 1 (14th March 2016) - Moilanen, Sanna; May, Vanessa; Räikkönen, Eija; Sevón, Eija; Laakso, Marja-Leena
Abstract : Purpose: – The purpose of this paper is to particularly focus on lone-mother families, comparing the childcare-related challenges experienced by working lone mothers and coupled mothers in three European countries in the context of a 24/7 economy and non-standard working hours (e.g. evening, night and weekend work). Design/methodology/approach: – This study utilises survey data from Finnish, Dutch and British working mothers ( n =1, 106) collected as part of the "Families 24/7" research project. Multivariate regression analysis is used to analyse the associations between childcare-related challenges, maternal non-standard working, lone motherhood and country of residence. Findings: – The results indicated similar results across the three countries by showing that working lone mothers experience childcare-related challenges more often compared with coupled mothers. Furthermore, an increase in maternal non-standard working associated positively with increased childcare-related challenges in both lone mother and coupled families but lone motherhood did not moderate this association. The findings suggest that, regardless of family form, families in all three countries struggle with childcare arrangements when the mother works during non-standard hours. This possibly relates to the inadequate provision of state-subsidised and flexible formal childcare during non-standard hours and to the country-specific maternal work hours cultures. Originality/value: – This study responds to the need for comparative research on the reconciliation of maternal non-standard working and childcare with self-collected data from three European welfare states. The importance of the study is further highlighted by the risks posed to the maintenance of maternal employment and family well-being when reconciliation of work and childcare is unsuccessful, especially in lone-mother families.